Preventive Behaviors Conveyed on YouTube to Mitigate Transmission of COVID-19: Cross-Sectional Study - Basch, Corey H; Hillyer, Grace C; Meleo-Erwin, Zoe C; Jaime, Christie; Mohlman, Jan; Basch, Charles E (JMIR Publications, 2020)
BackgroundAccurate information and guidance about personal behaviors that can reduce exposure to severe acute respiratory syndrome coronavirus 2 are among the most important elements in mitigating the spread of coronavirus disease 2019 (COVID-19). With over 2 billion users, YouTube is a media channel that millions turn to when seeking information. ObjectiveAt the time of this study, there were no published studies investigating the content of YouTube videos related to COVID-19. This study aims to address this gap in the current knowledge. MethodsThe 100 most widely viewed YouTube videos uploaded throughout the month of January 2020 were reviewed and the content covered was described. Collectively, these videos were viewed over 125 million times. ResultsFewer than one-third of the videos covered any of the seven key prevention behaviors listed on the US Centers for Disease Control and Prevention website. ConclusionsThese results represent an important missed opportunity for disease prevention.